Dermatological Manifestations in Chronic Kidney Disease Patients on Hemodialysis - Dorchhom Khrime; Alok Kumar; Nitin Bansal; Amar Nath Pandey; Anil Mehta; Jitendra Singh Bisth; Amit Verma (International Journal of Medical Research and Review, 2014)
Background and Objective: Chronic kidney disease patients on dialysis face various cutaneous problems. Common problems are xerosis, pruritus, pallor, pigmentation changes, hair changes and nail changes. We planned to look for cutaneous alterations in our patients on maintenance dialysis.Material and Methods: We included all patients on maintenance hemodialysis. We recorded their demographic profile and relevant investigations. All patients were examined by department of medicine and findings were confirmed by dermatologist. Specific investigations like skin biopsy, culture and sensitivity for bacterial infections, Gram's stain, potassium hydroxide mount and fungal culture were done where indicated.Results: There was one hundred forty patients. Mean age of patients was 38.7±7.4 years. Gender ratio was 1.32:1 (male: female). Mean duration of dialysis was 11.7±5.6 months. All patients had at least one cutaneous manifestation. Thirty four (24.28%) patients had two cutaneous manifestations. Twenty one (17.85%) patients had three or more cutaneous manifestations. Xerosis was seen in 74.8% patients. Pigmentary changes were seen in 43.57% patients. Nail changes were seen in fifty seven patients. Half and half nail was seen in twenty six (18.57%) patients. Hair changes were seen in forty nine (35%) patients. Cutaneous infections were seen in forty six patients. Most common infection was dermatophytosis in twenty eight patients (20%).Conclusion: CKD patients on dialysis suffer with multiple skin problems. Early detection of these problems like xerosis, cutaneous infection, and pruritus might result in improvement in quality of life.